2012
DOI: 10.1073/pnas.1121623109
|View full text |Cite
|
Sign up to set email alerts
|

The CD47-signal regulatory protein alpha (SIRPa) interaction is a therapeutic target for human solid tumors

Abstract: CD47, a "don't eat me" signal for phagocytic cells, is expressed on the surface of all human solid tumor cells. Analysis of patient tumor and matched adjacent normal (nontumor) tissue revealed that CD47 is overexpressed on cancer cells. CD47 mRNA expression levels correlated with a decreased probability of survival for multiple types of cancer. CD47 is a ligand for SIRPα, a protein expressed on macrophages and dendritic cells. In vitro, blockade of CD47 signaling using targeted monoclonal antibodies enabled ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
1,312
4
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,354 publications
(1,409 citation statements)
references
References 48 publications
40
1,312
4
4
Order By: Relevance
“…For example, Koh et al developed exosomes harbouring signal-regulatory protein alpha (SIRPα), and found that they exhibited augmented antagonizing activity against CD47–SIRPα interactions [121]. Emerging data suggest that the binding of tumour cell-surface CD47 to SIRPα on phagocytic cells can inhibit their phagocytic function [122]. Because CD47 is expressed on most cancer cell types, it represents a potentially tractable and widely applicable target for therapeutic blockade in cancer patients.…”
Section: Therapeutic Applications Of Surface-modified Evsmentioning
confidence: 99%
“…For example, Koh et al developed exosomes harbouring signal-regulatory protein alpha (SIRPα), and found that they exhibited augmented antagonizing activity against CD47–SIRPα interactions [121]. Emerging data suggest that the binding of tumour cell-surface CD47 to SIRPα on phagocytic cells can inhibit their phagocytic function [122]. Because CD47 is expressed on most cancer cell types, it represents a potentially tractable and widely applicable target for therapeutic blockade in cancer patients.…”
Section: Therapeutic Applications Of Surface-modified Evsmentioning
confidence: 99%
“…For in vivo bioluminescence imaging, RPMI 8226 cells were transduced with pCDH-CMV-MCSEF1-puro HIV-based lentiviral vector (Systems Biosciences, Mountain View, CA, USA) encoding eGFP and luciferase as described previously. 16 All human myeloma cell lines were cultured in RPMI 1640 medium (Invitrogen, Carlsbad, CA, USA) supplemented with 10% fetal bovine serum (FBS), Pen/ Strep (Invitrogen), GlutaMax (Invitrogen), sodium pyruvate (Invitrogen), non-essential amino acids (Invitrogen) and b-mercaptoethanol (Sigma, St Louis, MO, USA).…”
Section: Preparation Of Patient Bone Marrow Cellsmentioning
confidence: 99%
“…16 Mice were imaged 18 min after luciferin injection and total flux (photons/second) values were calculated within a region of interest corresponding to the anatomic region of tumor engraftment when peak radiance was achieved. Mice exhibiting comparable total flux values were then randomized into treatment groups and imaged weekly.…”
Section: Bioluminescent Imagingmentioning
confidence: 99%
See 2 more Smart Citations